Politologija v republiki Sloveniji - Lukšič, Igor (Teorija in praksa, 2022)
Political science only became a well-established scientific discipline in the world in the 20th century as a reflection and support for the processes of democratisation and decolonisation. The consolidation of the efforts to build the Slovenian nation state within the project of Yugoslav socialist self-MANAGEMENT and the deepening of non-party democracy led to the first institution being established for political science in Slovenia – the High School of Political Science. Back then, political science included the social sciences as a whole, namely: sociology, history, philosophy, psychology, economics and law. Political science has gradually become a narrower concept than the social sciences, and political science one of the social sciences. This is also shown by the naming of the faculty: from the High School of Political Science to the Faculty of Social Sciences. At the same time, the process of differentiation within political science began such that international relations, defence studies, policy analysis, public administration and political theory developed as independent fields in Slovenian conditions. These four areas have also designed special study programmes on the undergraduate, master’s and doctoral levels. Research centres in the field of political science are also organised in this way
Keywords: Politične vede